Pharmacokinetics of Olivamide after Bolus Administration in Rats and Rabbits (a Pilot Study) - Yu. A. Portnoy; S. A. Dovzhenko; M. B. Kobrin; M. I. Treshalin; V. A. Golobrodo; A. N. Tevyashova; A. A. Firsov (Антибиотики и Химиотерапия, 2020)
The pharmacokinetics of olivamide, a semisynthetic antitumor derivate of olivomycin A, were studied in rats and rabbits after bolus administration. Plasma concentrations of olivamide were determined by an HPLC assay. The decrease in olivamide levels in blood plasma was biphasic in both rats and rabbits. Olivamide levels declined slowly for up to 24 hours after a sharp drop in drug concentration during the first 15 minutes due to the rapid redistribution of olivamide between blood and peripheral tissues. The tissue availability of olivamide in rats ranged from 5700% (spleen) to 450% (liver). Eight-hour cumulative renal excretion of unchanged olivamide in rats was 18% of the dose. A three-exponential equation was used to describe pharmacokinetic profiles of olivamide in rat and rabbit plasma. The total clearance and steady-state volume of distribution in rats were higher than in rabbits (17.9-22.0 vs. 16.2 ml/(minXkg) and 7.8-8.7 vs. 5.1 l/kg, respectively). The mean retention time of olivamide in rabbits was less than in rats (5.3 vs 6.3-7.3 h). Olivamide pharmacokinetics in rats were linear.